Utilization of Poetry as a Learning Tool to Improve Speaking and Writing Skills in Elementary School Students. An Experimental Study - Apriliana, Nikita Dwi; Rokmanah, Siti; Syachruroji, A. (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Primary education is a critical stage in students' development, where speaking and writing skills play an important role in their communication development and self-expression. Poetry, as a form of literary art, offers potential that has not been fully explored as a learning tool in elementary schools. This research aims to investigate whether the use of poetry in learning can improve elementary school students' speaking and writing skills. The research method used was an experimental study with a pre-test and post-test group control design. The research sample consisted of two groups, namely the experimental group who received learning using poetry as a tool, and the control group who received conventional learning. Research participants were fourth grade elementary school students in two randomly selected schools. The research results showed that the experimental group who received learning using poetry experienced significant improvements in speaking and writing skills compared to the control group. Students involved in poetry learning show an increased ability to express their thoughts verbally and in writing more creatively and expressively. This research has important implications for basic education. Using poetry in learning can help students develop their speaking and writing skills, as well as increase their interest in literature. It also shows the potential for integrating literary arts in the elementary school curriculum as an effective tool for improving student communication. In conclusion, the use of poetry in elementary school learning can effectively improve students' speaking and writing skills. The results of this research provide a strong basis for considering the use of poetry as a creative and innovative learning tool in efforts to improve basic education.Keywords:Poetry, Learning Tools, Skills, Elementary School, Experimental.Abstrak Pendidikan dasar adalah tahap kritis dalam perkembangan siswa, di mana keterampilan berbicara dan menulis memainkan peran penting dalam perkembangan komunikasi dan ekspresi diri mereka. Puisi, sebagai salah satu bentuk seni sastra, menawarkan potensi yang belum sepenuhnya dieksplorasi sebagai alat pembelajaran di sekolah dasar. Penelitian ini bertujuan untuk menginvestigasi apakah pemanfaatan puisi dalam pembelajaran dapat meningkatkan keterampilan berbicara dan menulis siswa sekolah dasar. Metode penelitian yang digunakan adalah kajian eksperimental dengan desain kontrol kelompok pre-test dan post-test. Sampel penelitian terdiri dari dua kelompok, yaitu kelompok eksperimen yang menerima pembelajaran menggunakan puisi sebagai alat, dan kelompok kontrol yang menerima pembelajaran konvensional. Partisipan penelitian adalah siswa kelas empat sekolah dasar di dua sekolah yang dipilih secara acak. Hasil penelitian menunjukkan bahwa kelompok eksperimen yang menerima pembelajaran dengan pemanfaatan puisi mengalami peningkatan yang signifikan dalam keterampilan berbicara dan menulis dibandingkan dengan kelompok kontrol. Siswa yang terlibat dalam pembelajaran puisi menunjukkan peningkatan kemampuan untuk mengungkapkan pemikiran mereka secara lisan dan tertulis dengan lebih kreatif dan ekspresif. Penelitian ini memiliki implikasi penting untuk pendidikan dasar. Penggunaan puisi dalam pembelajaran dapat membantu siswa mengembangkan keterampilan berbicara dan menulis mereka, serta meningkatkan minat mereka dalam sastra. Hal ini juga menunjukkan potensi untuk mengintegrasikan seni sastra dalam kurikulum sekolah dasar sebagai alat yang efektif untuk meningkatkan komunikasi siswa. Dalam kesimpulan, pemanfaatan puisi dalam pembelajaran di sekolah dasar dapat efektif meningkatkan keterampilan berbicara dan menulis siswa. Hasil penelitian ini memberikan landasan yang kuat untuk mempertimbangkan penggunaan puisi sebagai alat pembelajaran yang kreatif dan inovatif dalam upaya meningkatkan pendidikan dasar.